Bioprocesses for Sustainable Bioeconomy: Fermentation, Benefits, and Constraints - Aslan, Emek; Sargin, Sayit (Springer International Publishing, 2023)
The bioeconomy concept is a path from a fossil-based system to a biobased one using renewable biological resources with a holistic approach. This concept aims for sustainable economic development by producing value-added products. The utilization of agro-industrial wastes for value-added end products focused on microbial fermentation. Industrial fermentation is the mass cultivation using cells in highly controlled, closed bioreactors. Although the basis of these bioprocesses depends on submerged fermentation (SMF), the solid-state fermentation (SSF) technique gained interest for producing several products in the last decades. The food and agricultural industries generate a considerable amount of agroindustrial wastes continuously which are rich in nutrients and have a high potential to be used as raw material. Food waste valorization is a potent tool for enabling the production of several products by benefiting the microorganisms and is a promising field from the bioeconomy perspective. Within the scope of this chapter, fermentation processes and applications, some of the value-added products related to the different biotechnology fields, and existing and potential integrated systems in terms of circular bioeconomy are examined by giving particular emphasis to SSF. © The Editor(s) (if applicable) and The Author(s), under exclusive license to Springer Nature Switzerland AG 2023.
Keywords: Bioeconomy; Fermentation; Food waste; Solid-state fermentation; Sustainability; Value-added product